Penggunaan Model Pembelajaran Berbasis Masalah dalam Meningkatkan Hasil Belajar Sejarah Kelas X di SMAN 1 Kupang - Hagur, Yasintus Reynaldus; Ndoen, Fransina A; Hadjoh, Adriana A (Universitas Nusa Cendana, 2024)
The aim of the research is to find out: (1). The process of using the Problem Based Learning Model in class X history learning at Kupang 1 State High School, (2). The use of the Problem Based Learning Model can improve history learning outcomes for class X at Kupang 1 State High School. The research method used is Classroom Action Research. This research consists of two cycles. Data collection techniques are carried out using tests and observations. The results of this research show that the learning outcomes of class X students at Kupang 1 State High School after implementing the problem-based learning model have increased. This can be proven from the learning results obtained by students in class X D. In class In cycle II, student learning outcomes experienced an increase in learning outcomes, all 36 students met the Minimum Completeness Criteria determined by the school.